Fourier transform infrared-attenuated total reflectance spectroscopy in conjunction with principal component analysis and soft independent modeling of class analogy to classify virgin coconut oil and coconut cooking oil. - Mission, Nathaniel Federizo
Fourier transform infrared -attenuated total reflectance spectroscopy in conjunction with principal component analysis and soft independent modeling of class analogy to classify virgin coconut oil and coconut cooking oil. c2009. 61 leaves. Undergraduate thesis. B.S. Chemistry. U.P. Visayas Abstract : This study investigates the potential of Fourier Infrared - Attenuated Total Reflectance Spectroscopy coupled with Principal Component Analysis (PCA) and Sof Independent Modeling of Class Analogies to authenticate and distinguish virgin coconut oil (VCO) from refined bleached and deodorized coconut oil (CCO). Commercially prepared VCO and CCO were used in the study. It was found out that medium resolution spectra of VCO and CCO yield distinct separation between these two classes at the spectral range 1800-1400cm-1. SIMCA was used to classify unknown samples and it showed that only pure samples can be classified by their respective classes.